Changes in the human gut microbiota composition caused by Helicobacter pylori eradication therapy: A systematic review and meta‐analysis. Issue 4 (9th June 2020) - Ye, Qunqun; Shao, Xiaona; Shen, Ruiwei; Chen, Dawei; Shen, Jianwei
Abstract: Background: The short‐term and long‐term effect of Helicobacter pylori ( H pylori ) eradication on the gut microbiota is controversial; hence, this study aimed to clarify changes in the gut microbiome and microbial diversity after H pylori eradication. Materials and Methods: Articles published in PubMed, MEDLINE, and EMBASE were searched up to March 20, 2020, with English‐language restriction. The outcomes including gut microbiota and alpha diversity were extracted to analysis. And then, Review Manager 5.3 software was used to conduct the data analysis. Results: At phylum level, next‐generation sequencing was performed. Meta‐analysis results showed that Actinobacteria decreased compared with baseline throughout the follow‐up period. Proteobacteria increased during short‐term follow‐up and then returned to normal. In addition, Bacteroidetes decreased and Firmicutes increased only during long‐term follow‐up. At family or genus level, conventional microbiological culturing was performed. Enterobacteriaceae and Enterococcus both increased during the short‐term and interim follow‐up. In addition, Lactobacillus only showed a decreasing trend during short‐term follow‐up, but it appeared statistical decreasing during interim follow‐up. Moreover, relatively sufficient evidence showed that alpha diversity decreased during short‐term follow‐up, and no reliable data were obtained to confirm the change of alpha diversity during interim and long‐term follow‐up. Conclusion: In different follow‐up periods after H pylori eradication, changes in gut microbiota were inconsistent. Microbial diversity decreased in the short‐term follow‐up, while there was no data to confirm subsequent alterations. The results provided a basis for the rational selection of probiotics in the eradication process. However, further studies are needed to obtain more clues.